2019
DOI: 10.1016/j.ica.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Copper complexes of multidentate carboxamide ligands

Abstract: The copper coordination chemistry of two multidentate carboxamido ligands derived from HL 1 (offering two quinolyl and one carboxamide donor) and H 4 L 2 (with two pyridine(dicarboxamido) units linked by naphthalene spacers) was explored. The former was chosen because upon deprotonation it would provide a monoanionic mer-coordinating N-donor set that would model the putative deprotonated form of the His-brace in copper monooxygenases, while the latter was designed to bind two copper ions and enable comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…One of the most interesting cases, in our opinion, is the complex of copper­(II), [CuL 2 ] ( 6 ), where L = multidentate carboxamido ligand, C 20 H 12 N 3 O 2 (Figure S9 in the Supporting Information). , The first study (crystal 6A , CSD: MIMDOE) revealed the crystal structure disordered over the pseudo-mirror plane perpendicular to the b axis, with the relative weight of the components amounting to ∼0.992/0.008. In the other structural determination, no disorder was found (crystal 6B , CSD: MIMDOE01).…”
Section: Results and Discussionmentioning
confidence: 99%
“…One of the most interesting cases, in our opinion, is the complex of copper­(II), [CuL 2 ] ( 6 ), where L = multidentate carboxamido ligand, C 20 H 12 N 3 O 2 (Figure S9 in the Supporting Information). , The first study (crystal 6A , CSD: MIMDOE) revealed the crystal structure disordered over the pseudo-mirror plane perpendicular to the b axis, with the relative weight of the components amounting to ∼0.992/0.008. In the other structural determination, no disorder was found (crystal 6B , CSD: MIMDOE01).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Numerous examples of both mononuclear and carboxylate-bridged dimers of Cu exist in the literature. 45 , 112 115 …”
Section: Resultsmentioning
confidence: 99%
“…The Cu­(I) ions adopt distorted trigonal planar geometries. The Cu–N lengths are typical for similar Cu­(I) complexes, ,,, and the Cu–Cu distance is 2.7509(7) Å, which is too long for significant bonding interactions between the two metals …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…European Journal of Inorganic Chemistry coworkers, [16] although in that case it was obtained from a Cu(I) carboxamide dimer. Both solid-state structures share the C2/c space group, although with different cell parameters.…”
Section: Accepted Manuscriptmentioning
confidence: 99%